2008
DOI: 10.1037/1938-8926.1.2.126
|View full text |Cite
|
Sign up to set email alerts
|

"Difficult yet rewarding": The experiences of African American graduate students in education at an Ivy League institution.

Abstract: This paper focuses on the experiences of African American students enrolled in a graduate program at an Ivy League institution, specifically those pursuing master's and doctoral degrees in the field of education. With a goal of helping to improve the persistence, retention, and success rates of African American graduate students, this study seeks to understand the following questions: What has been the nature of the graduate school experience for African American students in the field of education at an Ivy Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 37 publications
(105 reference statements)
11
95
0
Order By: Relevance
“…John, Paulsen, & Carter, 2005). Unlike the NIE Fellows who received generous financial support, African American graduate students studied by Gasman, Hirschfeld, and Vultaggio (2008) reported that financial struggles affected their ability to focus on their studies. Lack of funds to attend and present at conferences caused the students to miss prime networking opportunities, which subsequently hindered their search for jobs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…John, Paulsen, & Carter, 2005). Unlike the NIE Fellows who received generous financial support, African American graduate students studied by Gasman, Hirschfeld, and Vultaggio (2008) reported that financial struggles affected their ability to focus on their studies. Lack of funds to attend and present at conferences caused the students to miss prime networking opportunities, which subsequently hindered their search for jobs.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to pay for graduate education continues to be a significant concern for minority and women students (Gasman, Hirschfeld, & Vultaggio, 2008;Moyer, Salovey, & Casey-Cannon, 1999;St. John, Paulsen, & Carter, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Supervisors provide immediate and constructive feedback regarding a student's attempts to understand nature [16]. Supervisor who supervises doctoral students' professional development and formalizes their disciplinary identities during academic socialization experiences [17] is not easy to find due to supervising characterized as activities and interactions that may be related to work, skill development, and social or emotional sides of the supervisor [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through a critique of functionalist ideas about socialisation in higher education in particular (e.g. Gasman, Hirschfeld and Vultaggio, 2008;Sato and Hodge, 2009;Schneider, 2009) there has been an increased awareness and affirmation of diversity in academic contexts, including, for example, increasing openness to multilingual practices or linguistic variation in the ways students express understandings of disciplinary concepts and practices.…”
Section: A Theoretical Framework For Understanding Entry Into An Acadmentioning
confidence: 99%